Sialic acid, nutritional and fatty acid compositions of three species of freshwater fish eggs - Tham Wai Yeng; Ong Mei Kying; Teoh Chaiw Yee (BIO Web of Conferences)
This research aimed to determine the nutritional, sialic acid (SA) and fatty acid compositions of red hybrid tilapia (Oreochromis sp.), snakehead murrel (Channa striata), and sutchi catfish (Pangasius hypophthalmus) fish eggs. Eggs of P. hypophthalmus had the highest moisture (60.58%), ash (1.68%) and protein (25.19%) content while C. striata had the lowest moisture (48.58%), ash (0.81%) and protein (13.08%) content. Lipid content of C. striata fish eggs (35.94%) was significantly higher (p < 0.05) than Oreochromis sp. (14.23%) and Pangasius hypophthalmus (9.91%) fish eggs. Free sialic acid content of Oreochromis sp. (0.57 μg/mg) was significantly higher than Pangasius hypophthalmus (0.09 μg/mg) and Channa striata (0.11 μg/mg) fish eggs. Highest amount of saturated fatty acid was found in Pangasius hypophthalmus (44.04%) fish eggs, followed by Oreochromis sp. (37.69%) and Channa striata (24.40%) fish eggs. Monounsaturated fatty acid composition of Channa striata (45.53%) fish eggs was significantly higher than Oreochromis sp. (26.97%) and Pangasius hypophthalmus (23.33%) fish eggs. There was no significant difference (p > 0.05) of polyunsaturated fatty acid composition among three selected freshwater fish eggs. This study revealed that all selected freshwater fish eggs can be a source of major nutrients, SA and essential fatty acids.